Pancreaticoduodenectomy for the treatment of pancreatic neoplasms in children: A Pediatric Surgical Oncology Research Collaborative study. Issue 9 (13th July 2020) - Vasudevan, Sanjeev A.; Ha, Tu‐Anh N.; Zhu, Huirong; Heaton, Todd E.; LaQuaglia, Michael P.; Murphy, Joseph T.; Barry, Wesley E.; Goodhue, Catherine; Kim, Eugene S.; Aldrink, Jennifer H.; Polites, Stephanie F.; Leraas, Harold J.; et al.
Abstract: Background: To better characterize short‐term and long‐term outcomes in children with pancreatic tumors treated with pancreaticoduodenectomy (PD). Methods: Patients 21 years of age or younger who underwent PD at Pediatric Surgical Oncology Collaborative (PSORC) hospitals between 1990 and 2017 were identified. Demographic, clinical information, and outcomes (operative complications, long‐term pancreatic function, recurrence, and survival) were collected. Results: Sixty‐five patients from 18 institutions with a median age of 13 years (4 months‐22 years) and a median (IQR) follow‐up of 2.8 (4.3) years were analyzed. Solid pseudopapillary tumor of the pancreas (SPN) was the most common histology. Postoperative complications included pancreatic leak in 14% ( n = 9), delayed gastric emptying in 9% ( n = 6), marginal ulcer in one patient, and perioperative (30‐day) death due to hepatic failure in one patient. Pancreatic insufficiency was observed in 32% ( n = 21) of patients, with 23%, 3%, and 6% with exocrine, or endocrine insufficiencies, or both, respectively. Children with SPN and benign neoplasms all survived. Overall, there were 14 (22%) recurrences and 11 deaths (17%). Univariate analysis revealed non‐SPN malignant tumor diagnosis, preoperative vascular involvement, intraoperative transfusion requirement, pathologic vascular invasion, positive margins, and need for neoadjuvant chemotherapy as risk factors for recurrence and poor survival. Multivariate analysis only revealed pathologic vascular invasion as a risk factor for recurrence and poor survival. Conclusion: This is the largest series of pediatric PD patients. PD is curative for SPN and benign neoplasms. Pancreatic insufficiency is the most common postoperative complication. Outcome is primarily associated with histology.